CHEMICAL COMPOSITION AND HEALING PROPERTIES (Zingiber officinaie) (American Journal of Interdisciplinary Research and Development, 2023)
This research work is devoted to the extraction of biologically active substances from the medicinal plant ginger (Zingiber officinale), amino acids in extracts and analysis of the results obtained.